Conceptual Analysis of It Media Integration In The Digital Islamic Education Curriculum As An Effort To Strengthen The Character Of Junior High School Students: A Library Perspective - Syaifuddin, Syaifuddin; Junaedi, Junaedi (Jurnal Edusci, 2025)
Background. Digital transformation in the world of education demands a shift in the learning paradigm of Islamic Religious Education (PAI), particularly in strengthening the character of junior high school students. Aims. This research aims to formulate a conceptual model for the integration of information technology (IT) media into the digital PAI curriculum as an instrument for the formation of Islamic character. Methods. Using a qualitative approach through library research and descriptive-analytical methods, this study analyzes academic literature from the past decade using content analysis and thematic analysis techniques. Result. The study results in the ISLAMIC-TECH model, which includes five main components: Infrastructure, Spiritual Content, Learning Activity, Assessment, and Moral Character, as an integrative foundation between technological, pedagogical, and spiritual dimensions. Four effective IT media typologies in PAI learning have been identified, namely: immersive media (VR/AR), interactive (gamification), collaborative (social learning), and adaptive (personalized learning). The implementation strategy emphasizes the principle of "Technology as Servant, Spirituality as Master" and dual-mode learning to maintain a balance between digital interaction and direct religious practice. Conclusion. The identified challenges include limited infrastructure, teachers' digital competencies, and difficulties in integrating pedagogy and spirituality. Nevertheless, the integration of IT media has proven capable of increasing student engagement with PAI material, facilitating the development of digital wisdom, and strengthening character dimensions through critical thinking skills, collaboration, and spiritual literacy. Implementation. This research provides a theoretical contribution in the form of a conceptual framework for a technology-based digital PAI curriculum that is contextual, authentically Islamic, and adaptive to the needs of the 21st century